Digital Health Integration in the Clinical Practice: A Review of Technological Innovations in Nursing - Aeshah Abdu Ahmed Hadadi, Fatimah Hassan Al Abbas, Afnan Ali Ahmed Almusharraf, Layla Hassan Ghanem Alghanem (International Journal of Scientific Research and Innovative Studies, 2024)
An in-depth digital transformation is being experienced in the healthcare industry, and nursing is the leading sector undergoing this technological revolution. Digital health tools- e.g. electronic health records (EHRs), telehealth applications, mobile health applications, clinical decision support systems are transforming the nursing sector of care delivery, clinical reporting functions, and patient engagement. In the current literature review, the researcher intends to examine how digital health innovations can be integrated into nursing practice and discuss such main areas of use, obstacles and catalysts of implementation, and clinical and organizational impact. The study is a collection of findings of a systematic literature review of peer-reviewed studies indexed in 3 databases, Scopus, PubMed, and, CINAHL included in the study; published between 2013 and 2024. According to the analysis, along with exhibiting improvements in care-coordination, documentation accuracy, and patient engagement, digital tools present issues that are connected with usability, workflow breach, data privacy, and digital literacy. The review has concluded that there should be an outline of the significance of nurse-led co-design and targeted digital education with the help of regulatory provisions to make the digital integration in the practices of the clinical nurses sustainable. Keywords: digital health, informatics nursing, telehealth, clinical decision support, electronic health records, digital transformation, eHealth, technology adoption, nursing practice. Received Date: February 25, 2024 Accepted Date: March 12, 2024 Published Date: April 17, 2024 Available Online at https://www.ijsrisjournal.com/index.php/ojsfiles/article/view/395 https://doi.org/10.5281/zenodo.15798263